BASIC STAGES AND PROMINENT FIGURES IN HISTORY OF UKRAINIAN FOLCLORISTICI - Didic, O. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The reflections after the book of Yaroslav Garasim are «Essays to history of Ukrainian folkloristic» – К.: Knowledge, 2009, – 301 s.